Highlighting early detection of thyroid pathology and gestational diabetes effects on oxidative stress that provokes preterm delivery in thyroidology: Does that ring a bell? - Dugalic, Stefan; Todorovic, Jovana; Sengul, Demet; Sengul, Ilker; Veiga, Eduardo Carvalho de Arruda; Plesinac, Jovana; Petronijevic, Milica; Macura, Maja; Kepeci, Sonja Perkovic; Milinčić, Miloš; Pavlovic, Andrija; Gojnic, Miroslava (Clinics, 2023)
Objectives: Ad fontes, the status of the thyroid gland, and metabolic disturbance lead to the alteration of oxygenation. In pregnancy, it is particularly crucial to possess all predictive parameters. Methods: This cross-sectional study was conducted at the Clinic of Gynecology and Obstetrics, Clinical Center of Serbia, Belgrade, Serbia, between 2017 and 2021 which study included a total of 99 women who had been admitted for preterm delivery and had undergone thyroid analysis, detected Hashimoto thyroiditis, and Oral Glucose Tolerance Test (OGTT) 40 days after delivery and had pathological Homeostatic Model Assessment for Insulin Response (HOMA IR) indices. In the group of urgent patients with preterm delivery, we looked after not only routine Doppler of the umbilical artery, but we measured specific ratios such as the Cerebroplacental ratio (CP). Results: The mean maternal age was 32.23 ± 5.96 years and the mean gestational age was detected as 35.40 ± 2.39 weeks. The delivery was completed vaginally in 77 women (78%) and surgically in 22 (22%). The Mean APGAR score was 8.44 ± 1.18, the mean birth weight was 2666.87 ± 622.17g and the cases undergoing cesarean section had significantly higher values of pulsatility index (1.85 ± 0.27 vs. 1.34 ± 0.31) and CP (1.22 ± 0.26 vs. 0.47 ± 0.17). Conclusions: The introduction of Doppler sonography for blood flow assessment helps to form a complete clinical description of the patient, particularly in conditions where oxidative stress became provocative by the thyroid gland antibodies and gestational diabetes in Thyroidology.